INKLUSI KEUANGAN SEBAGAI VARIABEL MODERASI TERHADAP MINAT PINJAMAN ONLINE PADA KARYAWAN GENERASI Z DI KOTA SURABAYA - Dhika Hanggara Putra; Tri Kartika Pertiwi (Universitas Sarjanawiyata Tamansiswa, 2025)
Fintech provides solutions for society by offering various conveniences in accessing digital financial services, one of which is online lending. Behind the convenience offered, there are also accompanying risks. Low levels of financial literacy and a high lifestyle tendency are among the causes of the widespread use of online loans, particularly among Generation Z. This study aims to analyze the relationship between financial literacy, a hedonism lifestyle, and financial inclusion toward the interest in using online loans. This research employs a quantitative method with a total of 139 respondents selected from Generation Z employees in Surabaya City, chosen based on specific sampling criteria. Data analysis was conducted using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). The results indicate that financial literacy has a significant negative effect on the interest in online loans, while a hedonism lifestyle has a significant positive effect on the interest in online loans. Financial inclusion is unable to moderate the relationship between financial literacy and interest in online loans. Financial inclusion strengthens the influence of a hedonism lifestyle on interest in online loans. These findings highlight the importance of lifestyle management and optimizing financial literacy to ensure sound financial management, thereby avoiding risks in utilizing and engaging with fintech services.